2007
DOI: 10.1002/aic.11329
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization of fine and ultrafine particles using nitrogen and neon as fluidizing gases

Abstract: in Wiley InterScience (www.interscience.wiley.com).When fluidized by a gas, some agglomerated fine and ultrafine particles display a regime of uniform, nonbubbling fluidization known as agglomerate particulate fluidization (APF). The agglomeration of micrometric sized particles, or simple pre-existing agglomerates in the case of nanoparticles, is governed by the balance between hydrodynamic shear forces and interparticle attractive forces. From this balance the theoretical scaling law Bo g $ k D12 has been der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 48 publications
6
42
0
Order By: Relevance
“…Eq. (1) has been fitted to experimental data, which has served to infer an average value of the agglomerate size in fluidized beds, which has yielded results in accordance with independent direct experimental observations (Castellanos et al, 2001;Nam et al, 2004;Zhu et al, 2005;Valverde et al, 2008). Yao et al (2002) observed that 7-16 nm silica particles formed multi-stage agglomerates (MSA) in the fluidized bed by three steps.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Eq. (1) has been fitted to experimental data, which has served to infer an average value of the agglomerate size in fluidized beds, which has yielded results in accordance with independent direct experimental observations (Castellanos et al, 2001;Nam et al, 2004;Zhu et al, 2005;Valverde et al, 2008). Yao et al (2002) observed that 7-16 nm silica particles formed multi-stage agglomerates (MSA) in the fluidized bed by three steps.…”
Section: Introductionsupporting
confidence: 60%
“…From these values it is calculated F * vdW ∼ 10 nN. Using a typical value of d * =30 m for the size of the simple-agglomerates, as inferred from the work of Nam et al (2004), and D a = 2.5, as inferred from settling experiments Valverde et al, 2008;Wang et al, 2006a), Eq. (2) predicts d * * 150 m for 10 nm silica nanoparticles ( p = 2500 kg/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The vibration energy is mostly absorbed by the agglomerates on the surface of the fluidized bed [22]. Even though the Richardson-Zaki equation has mainly been applied to describe the bed expansion of liquid fluidized beds [6], its general form has also been successfully applied to beds exhibiting strong interparticle forces [11,15,19,23]. The equation relates the superficial fluid velocity, U g , with the bed voidage, e, and the terminal velocity for a single particle, U t , as given by Eq.…”
Section: Model Derivationmentioning
confidence: 99%
“…Valverde et al [7][8][9][10] extensively explored this approach based on a modified Richardson-Zaki equation to estimate the subagglomerate size. Following this, the method was used to estimate the agglomerate sizes of nanoparticles [11].…”
Section: Introductionmentioning
confidence: 99%
“…4,5,48 Although the fractal dimension is often treated as a constant independent of the agglomerate size, it has been shown that the agglomerates composed of natural kaolinite particles were better represented by a variable fractal dimension. [49][50][51] Such variable fractal dimension would further complicate the estimate for agglomerate density.…”
Section: Aps Size Analysismentioning
confidence: 99%